Analysis of the degree of job satisfaction of the itinerant hearing and speech teacher (European Journal of Education and Psychology, 2015)
With twenty years of business and professional development since the emergence of the itinerant speech and hearing teacher (AL), it seems appropriate to reflect on the role this figure has been playing in order to apprehend the things considered to improve the approach to promote the quality of its educational performance. Moreover, we currently find ourselves in a process of university reform that will affect the whole of the professional roles of teachers in the XXI century, contributions being required to delineate and strengthen the field of attention to diversity in the initial training of teachers, as college majors that were responsible for such action disappear. This study aims to contribute to the understanding of the reality of the educational activities of these professionals with an analysis of the degree of job satisfaction that is denoted in this group relative to the work being done in schools.